CARACTERÍSTICAS SOCIODEMOGRÁFICAS E COMORBIDADES DA PESSOA IDOSA ASSOCIADAS À QUALIDADE DA ATENÇÃO PRIMÁRIA À SAÚDE - Rivas, Claudia Maria Ferrony (2024)
The continuous assessment of the quality of services provided by Primary Health Care (PHC), using tools like the Primary Care Assessment Tool (PCATool), is essential for improving services and addressing the needs of the population based on epidemiological data and local diagnoses. In this regard, the present study aimed to evaluate the quality of PHC in the municipality of Santa Maria/RS through the perception of the elderly population and to analyze its possible associations with sociodemographic characteristics and comorbidities. This is a cross-sectional study with a quantitative approach, conducted with 249 elderly individuals (60 years of age or older) registered in 25 Family Health Strategies (ESFs) in the municipality of Santa Maria, RS. The PCATool-Brazil was used as the instrument for assessing Primary Health Care, along with a questionnaire to gather sociodemographic information. The scores of the essential attributes were compared with the sociodemographic data and comorbidities of the study participants. Regarding sociodemographic characterization, most participants were female, with education levels ranging from 0 to 8 years and family income between one and two minimum wages. The average age of the elderly participants in the study was 69.7 ± 6.9, ranging from 60 to 90 years old. The overall average PHC evaluation scores from the elderly perspective were considered satisfactory at 7.5 ± 1.2. Satisfactory scores were found in first contact access (utilization), longitudinality, coordination (integration of care and information systems), and comprehensiveness (services provided). Unsatisfactory scores were obtained in the essential attributes of first-contact access (accessibility) and comprehensiveness (available services). A significant association was observed between gender and the essential attributes of accessibility, longitudinality, and services provided, with these attributes being better evaluated by elderly men. A significant association was found between the age group of 60 to 69 years and the essential attribute of information systems, as well as a significant association between the attributes of available services and provided services and family income of three or more minimum wages. Regarding comorbidities reported by the elderly, most had systemic arterial hypertension (SAH), followed by diabetes mellitus (DM) and arthritis/arthrosis. An association was observed between the presence of comorbidity and the evaluation of the attributes of longitudinality and information systems. Elderly individuals with DM demonstrated lower scores in the attribute of available services compared to those without diabetes. Lower scores were also observed in elderly individuals with arthritis in the attributes of accessibility and integration of care. Research participants with SAH better evaluated the services of first-contact access - utilization, longitudinality, and information systems. It was evidenced that although PHC in Santa Maria (RS, Brazil) is generally evaluated as satisfactory by the elderly population served in the FHS, there are specific areas, such as accessibility and comprehensiveness of available services, that need improvements. Sociodemographic variables and the presence of comorbidities significantly influence the perception of health service quality. Thus, it is essential to consider these differences to improve the quality of PHC and more effectively meet the needs of the elderly population.